Adolescent gynaecology - Michala, L.; Creighton, S. (Obstetrics, Gynaecology and Reproductive Medicine, 2014)
Adolescent gynaecology is increasingly recognized as an area in which specific knowledge and expertise is required to ensure that patients achieve the best outcome. Gynaecological problems in adolescents are common, and although serious pathology is rare, distress and discomfort can be significant. Adolescent girls are under greater pressure than ever before, particularly in terms of examination performance; they find menstrual dysfunction particularly difficult to manage. Careful and sympathetic assessment is crucial, and simple treatment remedies may be all that is required. However, complex and rare medical conditions can also occur and must not be missed. Some congenital disorders present for the first time in adolescence. Early detection and appropriate treatment will ensure the best possible outcomes in terms of sexual function and potential fertility. © 2014 Elsevier Ltd.
Keywords: Adolescent gynaecology; Menstrual dysfunction; Polycystic ovary syndrome; Rokitansky syndrome; Turner syndrome